International Negotiation: Analysis, Approaches, IssuesInternational Negotiation: Analysis, Approaches, Issues, edited by KremenyukVictor A.. San Francisco: Jossey-Bass, 1991, 486 pp., cloth. - Weiss, Stephen E. (Academy of Management Review, 1992)
This article presents a review of the book &International Negotiation: Analysis, Approaches, Issues,& edited by Victor A. Kremenyuk.